Uncivilizing : [a collection of poetry] - Davidson, Caroline (Caroline H.); Footman, Jennifer, 1942- (Insomniac Press, 1997)
In a dehumanizing world where commodities and materialism seem to be more valuable than people, six poets have assembled a collection of their work that acts as an antidote to the market-driven '90s. Caroline Davidson, Roger Nash, Sonja Dunn, James Reaney, Bernice Lever and Robert Sward bring you Uncivilizing, a book of poetry that will inspire you to free yourself from the traps of everyday life.